Analisis Polimorfisme Genetik Anopheles Aconitus DOnitz (Diptera:.Culicidae) Dart Daerah Istimewa Yogyakarta Dan Jawa Tengah Dengan Random Amplified Polymorphic Dna (Rapd) - Pcr - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The objective of this research was to investigate genetic polymorphism of mosquito Anopheles aconitus Donit: from coastal area (Patehan & Panjatan), lowland (Salaman & Mingg-ir) and upland (Sawangan & Pakem) using RandOm Amplified Polymorphic DNA - Polymerase Chain Reaction (RAPD-PCR). The research was conducted at the Biochemistry Laboratory, lnter-University Center, Gadjah Mada University, Yogyakarta on February - Juli 2000. The research was conducted in two steps, i.e. field collection of mosquitoes and DNA isolation based on the procedure given by Hoelzel (1994) with modification by Anggreini (1998), DNA amplification and electrophoresis in the laboratory. The research used three primer, i.e. E-16, E-17 and F-04. The results of this research indicated that the specific DNA bands to the whole research locations were 227 by (base pair), 303 by and 436 by (E-16), 364 bp, 1005 bp, and 2983 by (E-17). Thus, these primers were potentially to be used for identification (taxonomic keys) of the An. aconitus. The specific bands for mosquitoes sample from each research location were not found. Genetic variation of An. aconitus from coastal area, lowland and upland was genotype polymorphism (intrapopulation). Quantitative DNA bands analysis indicated that the sample of mosquito from coastal area had the highest level, i. e. 80%, then consecutively followed by samples of mosquito from upland and lowland being 73,13% and 72,93% respectively.